THE ANALYSIS OF IMPOLITENESS UTTERANCES AS REFLECTED IN “THE WRONG STEPMOTHER" MOVIE - Jojor Romanna Simanjuntak; Mhd. Johan (eScience Humanity Journal, 2022)
This study aimed to analyze the impoliteness utterance that reflected in literary work, especially in a movie. The data source used in this article is The Wrong Stepmother Movie. This research used the theory of Pragmatic related with impoliteness and Culpeper (2011). The method used in this research is Qualitative method. From the research analysis and finding it can be concluded. All strategies and types of impoliteness are found in “The Wrong Stepmother” movie. These are bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm, or mock politeness and last withhold politeness. From the findings, there were found strategies that often occurred which is positive impoliteness with the total 13 data or 39%, followed bald on record impoliteness with 7 data or 21%, sarcasm or mock politeness with 7 data or 21%, negative impoliteness with 4 data or 13%, and the last is withhold politeness least used with 2 data or 6%. The types of impoliteness found in this research were also found. These are affective impoliteness with 18 data or 58%, next coercive impoliteness with 7 data or 23%, and last is entertaining impoliteness with 6 data or 19%. The most dominant occurred in strategy impoliteness is positive impoliteness and in types of impoliteness is affective impoliteness.